Pengaruh Acidifier Terhadap Performa Produksi Dan Analisis Usaha Pada Ayam Pedaging Yang Diinfeksi Avian Pathogenic Escherichia coli (APEC) : The Effect of Acidifier on Production Performance and Business Analysis of Broiler Chickens Infected with Avian Pathogenic Escherichia coli (APEC) - Silfia, Himatul Ilma; Warsito , Sunaryo Hadi; Mufasirin; Hidanah , Sri; Lokapirnasari, Widya Paramita; Yudaniayanti , Irasari; Firdaus , Muhammad Aviv; Lisnanti, Ertika Fitri (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2024)
This study aimed to provide the impact of acidifier supplementation on feed consumption, body weight gain (BWG), feed efficiency, and feed conversion ratio (FCR) in broiler chickens infected with Avian Pathogenic Escherichia coli (APEC). The use of acidifiers is proposed as a potential solution to improve gut health and nutrient absorption. This study employed a completely randomized design (CRD). Forty broiler chickens, ages 1 to 35, were utilized in this study, and the treatment started at 8 days of age. There were 5 treatments and 4 replications for each treatment, with 2 broiler chicks in each replication. The treatments consisted of negative control, without APEC infection (P0), positive control, with APEC infection (P1), infected with APEC with 0.1% of Antibiotic Growth Promoters in the diet (P2), and infected with APEC with additional feed acidifier 0.5% (P3). This study analyzed its effect on feed consumption, Body Weight Gain (BWG), Feed Conversion Ratio (FCR), and feed efficiency. Also, the business analysis was carried out by calculating the contribution margin (CM). Data was statistically analyzed using one way-analysis of variance (ANOVA), followed by Duncan's multiple range test to determine any statistical differences (p<0.05). The research results show that adding an acidifier to the diet does not reduce the feed consumption value but can increase BWG, reduce the FCR value (p<0.05), improve feed efficiency, and increase the contribution margin in broiler chicken farming. It concludes that adding 0.5% acidifier to the feed can improve broiler chickens infected with APEC production performance.